Heart Rate Variability: A Potential Tool for Monitoring Immunomodulatory Effects of Parenteral Fish Oil Feeding in Patients With Sepsis. (May 2019) - Papaioannou, Vasilios; Pnevmatikos, Ioannis
Fish oil, rich in the very-long chain omega (ω)-3 polyunsaturated fatty acids (PUFAs), has been found to have immunomodulatory effects in different groups of critically ill patients. In addition, its parenteral administration seems to attenuate the inflammatory response within 2 to 3 days. The activation of the cholinergic anti-inflammatory pathway has been suggested to mediate such immunoregulatory effects. As different experimental studies have convincingly illustrated that enhanced vagal tone can decrease pro-inflammatory cytokine secretion, novel monitoring tools of its activity at the bedside could be developed, to evaluate nutritional manipulation of immune response in the critically ill. Heart rate variability (HRV) is the variability of R-R series in the electrocardiogram and could be a promising surrogate marker of immune response and its modulation during fish oil feeding, rich in ω-3 PUFAs. Heart rate variability is an indirect measure of autonomic nervous system (ANS) output, reflecting mainly fluctuations in ANS activity. Through HRV analysis, different "physiomarkers" can be estimated that could be used as early and more accurate "smart alarms" because they are based on high-frequency measurements and are much more easy to get at the bedside. On the contrary, various "biomarkers" such as cytokines exhibit marked interdependence, pleiotropy, and their plasma concentrations fluctuate from day to day in patients with sepsis. In this respect, an inverse relation between different HRV components and inflammatory biomarkers has been observed in patients with severe sepsis and septic shock, whereas a beneficial effect of ω-3 PUFAs on HRV has been demonstrated in patients with cardiovascular diseases. Consequently, in this article, we suggest that a beneficial effect of ω-3 PUFAs on HRV and clinical outcome in patients with sepsis merits further investigation and could be tested in future clinical trials as a real-time monitoring tool of nutritional manipulation of the inflammatory response in the critically ill.